The Damaging Effects of Perceived Crocodile Tears for a Crier’s Image - van Roeyen, Inge; Riem, Madelon M. E.; Toncic, Marko; Vingerhoets, Ad J. J. M. (Frontiers in Psychology, 2020)
Emotional tears are uniquely human and play an essential role in the communication of distress in adults. Several studies have shown that individuals are more willing to offer emotional support and help a person in tears. Preliminary evidence suggests that this greater willingness to provide support is mediated via perceived warmth and helplessness. Moreover, tearful individuals are regarded as more reliable and honest. In the current study, we examined whether people can reliably distinguish genuine and fake crying, and what the further consequences for the evaluation of the crier are. A total of 202 participants (73 men, 129 women) were exposed to brief movie clips of genuine and fake crying adults and were asked to evaluate the criers. Results show that women were slightly better at identifying fake and genuine crying. How the crying was perceived subsequently seemed to have a strong influence on the further evaluation of the "crier." Criers regarded as pretenders were perceived as significantly more manipulative, less reliable, less warm, and less competent. Further, the respondents felt less connected with the perceived pretenders, who were less welcomed as friends, colleagues, neighbors, and babysitter. They were also qualified as significantly less fit for "reliable" professions (judge, teacher, police officer, scientist, and physician). In contrast, the ratings of their fitness for "unreliable" professions (banker, CEO, journalist, real estate salesman, and politician) yielded a significant difference in only one video clip (and contrary to expectations). Our findings thus indicate that the subjective labeling of crying as fake is associated with a significantly less positive perception of the "crying" person, regardless of whether the crying is actually fake or genuine. Crocodile tears thus seem to be associated with a severe risk of a damaging effect for a crier's image.